The Effects of Palm Oil on Plasma and Serum Lipid Parameters: A Systematic Review on Animal Intervention Studies - Syarifah-Noratiqah, Syed-Badrul; Fairus, Syed; Zulfarina, Mohamed S.; Nasrullah, Zafri; Qodriyah, H. M. S.; Naina-Mohamed, Isa (Frontiers in Veterinary Science, 2020)
Background: Accumulative evidences on the beneficial effects of palm oil are progressively reported; however, there are still several controversies related to their effects on the risks of cardiovascular disease (CVD). This review explores the effects of palm oil and its liquid fraction namely palm olein, which is commonly used as cooking oil on four lipid parameters; total cholesterol (TC), triglyceride (TG), high-density lipoprotein-cholesterol (HDL-C) and low-density lipoprotein-cholesterol (LDL-C) that play an important role as CVD-related biomarkers. A systematic review of the literature was conducted to identify the relevant studies on palm oil and the lipid parameters specifically focusing on the in-vivo animal model. Methods: A comprehensive search was conducted in Medline via EBSCOhost, Medline via OVID and Scopus. Studies were limited to the English language published between the years of 2000 to 2019. The main inclusion criteria were as follow: (1) study with in-vivo animal experiments [the animal should be limited to mammals] (2) Study should have evaluated the effects of palm oil or palm olein on plasma or serum lipid parameter (3) Study should have used palm oil or palm olein in the form of pure or refined oil (4) The treatment of palm oil or palm olein was assessed using the following outcomes: plasma or serum TC, TG, HDL-C and LDL-C concentration (5) Study should have control group and (6) studies on specific fatty acid, fraction enriched tocotrienol and tocopherol, crude palm oil, karnel oil, red palm oil, thermally oxidised palm oil, hydrogenated palm oil and palm oil or palm olein based products namely margarine, palm milk, butter and cream were excluded. The quality and the risk of bias on the selected studies were assessed using ARRIVE Guideline and SYRCLE’s Risk of Bias tools respectively. Results: The literature search successfully identified 17 potentially relevant articles, whereby nine of them met the inclusion criteria. Conclusion: Significant positive outcomes were observed in several lipid parameters such as TC and LDL-C. The evidence from this review supported that palm oil and palm olein possess high potential as lipid-lowering agents.